Machine‐readable universal data format for bidirectional reflectance distribution function and BiRDview—An open‐source web‐based application for viewing and comparing bidirectional reflectance data. Issue 5 (11th March 2022) - Lanevski, Dmitri; Ferrero, Alejandro; Perales, Esther; Manoocheri, Farshid; Ikonen, Erkki
Abstract: Modern studies of bidirectional reflectance distribution function (BRDF) and its applications using data and machine‐driven science require formatting of BRDF data according to Findable, accessible, interoperable and reusable (FAIR) data principles. As a solution a FAIR universal BRDF file‐format based on Java Script Object Notation (JSON) is proposed. JSON principles as well as file structure are explained and examples are given. Automatic validation of universal BRDF file format is realized with the help of JSON schema. Furthermore, the source code and accompanying documentation are presented in dedicated supporting material files . It is expected that after its wide adoption, the proposed BRDF file format will enhance collaboration between different research groups and benefit machine‐driven science. The uptake is facilitated by introducing a BiRDview—a modern open‐source web‐based application for BRDF visualization. Abstract : Visual interface of BiRDview. Example data is presented from BRDF measurements of an actual ceramic white tile sample. BRDF, bidirectional reflectance distribution function